Evaluasi dan Perkembangan Ketahanan Pangan Indonesia Tahun 2023–2025 berdasarkan Kerangka Empat Pilar FAO - Nabilah Zahra Tiftazani; Muhammad Rifkie Sabitul Noerzaman; Cika Gracella Hermawan; Nada Askori; Maulidia Iftitakhur Rohmah; Andi Setiawan (PT. Hasba Edukasi Mandiri, 2025)
Food security is a critical and crucial issue for Indonesia, facing multidimensional challenges such as climate change, import dependence, and inequality in distribution processes. This study aims to evaluate the development of Indonesia's food security between 2023 and 2025 using the FAO's four pillars framework (Availability, Accessibility, Utilization, and Stability). The research method used is descriptive qualitative, utilizing secondary data from various government reports and international institutions. The research results show that Indonesia's food security is in a state of